APPLICATION OF MODERN BREEDING METHODS TO DAIRY CATTLE - S. V. Titova (Вавиловский журнал генетики и селекции)
Biological and breeding parameters of populations of black-and-white cattle have been studied by using a genetic-mathematical model to identify the optimal ratio of variable and fixed factors in the optimization of breeding programs. The influence of the variables (the number of replacement bull fathers, the proportion of cows of the active part of the population fertilized with sperm of checked bulls, the number of effective daughters, and a bank for long-term storage of sperm for each checked bull) on the genetic progress has been investigated.